Test and design of eccentrically-loaded slender circular tubed columns filled with high-strength concrete and reinforcement. (May 2023) - Li, Xiang; Liu, Jiepeng; Wang, Xuanding; Chen, Y. Frank
Abstract: The tubed-reinforced concrete (TRC) column is an original reinforced concrete column in which the stirrups are mostly replaced with the steel tube to enhance the confinement to the concrete core. In this study, the eccentrically-loaded behavior of slender circular TRC (CTRC) columns with high-strength materials was experimentally and numerically investigated. Six slender columns with high-strength concrete of 81 MPa and high-strength rebar of 583 MPa were tested to failure under eccentric loading, considering the main parameters of length-to-diameter ratio and load eccentricity. A three-dimensional finite element (FE) model was established and verified for conducting parametric studies and investigating the moment magnification and eccentricity magnification which reflect the second-order effect on the strength of slender columns. The results indicate that all columns fail in a bending mode and show good deformability, even with the use of high-strength materials, and the strength of high-strength rebars can be fully utilized due to the enhanced concrete compressive strain and ductility. Based on the test results and parametric study, a design method is proposed to assist designers to evaluate the load capacity of slender CTRC columns.